DIFERENTIATED INSTRUCTION: USING THEORY OF MULTIPLE INTELLIGENCE TO ENHANCE ACADEMIC ACHIEVEMENT OF GRAGUATE STUDENTS - Afshan, Shazia; Khanam, Afifa; Aziz, Fakhra (International Journal of Psychosocial Rehabilitation, 2020)
Students at higher education come from diverse socioeconomic backgrounds with distinct potentials and need to be catered differently. Their interests, capacities and aptitudes require differentiated instruction to match their learning styles befittingly. The current study was designed to apply theory of multiple intelligence to enhance academic achievement of graduate students by using differentiated instruction. This quasi experimental study was conducted on graduating students of a women college at district Lahore, Pakistan. The study group was consisted of 80 students out of which 40 students were in experimental group and 40 students were regarded as control group. A ‘pre-test, post-test control group design’ was used to introduce intervention to the experimental group by teaching through differentiated instruction based on Howard Gardner’s theory of multiple intelligence. The control group received traditional chalk and talk method. The analysis of pre and post tests was made through paired and independent sample t-test. The results of experimental group revealed a substantial increase in the academic achievement of graduate students as compared to the control group. The study provides evidence that differentiated instruction contributes in students’ learning and produces a positive environment. The study also suggests the use of differentiated assessment for measuring individual academic achievement and performance. There are underlined implications of the study for a comprehensive curriculum giving space to individual capacities.